PENGARUH PERCEIVED USEFULNESS TERHADAP CONTINUANCE INTENTION TO USE PADA PENGGUNA MOBILE PAYMENT DANA DENGAN SATISFACTION SEBAGAI VARIABEL MEDIASI - Pradana, Wilky Yondi; Yolanda, Mike (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2024)
The purpose of this study is to analyze (1) the effect of perceived Usefulness on continuance intention to use (2) the effect of perceived Usefulness on satisfaction (3) the effect of satisfaction on continuance intention to use (4) the effect of perceived Usefulness on continuance intention to use with satisfaction as a mediation variable. this type of research is quantitative descriptive research, the number of samples in this study is 144 respondents using techniques purposive sampling, data analysis method using SEM analysis using Smart PLS 4 applications. The results of the study are (1) there is a significant influence between perceived Usefulness on continuance intention to use (2) there is a significant influence between perceived Usefulness on satisfaction (3) there is a significant influence between satisfaction on continuance intention to use (4) there is a significant influence between perceived Usefulness on continuance intention to use with satisfaction as a mediation variable.